Alterações fisiológicas, anatômicas e produtivas do feijoeiro induzidas por Trichoderma spp. E fosfito de potássio em resposta ao ataque de Colletotrichum lindemuthianum - Figueira , Eliana Peliçon Pereira (2018)
In Brazil, common bean (Phaseolus vulgaris L.) cultivation shows a great socioeconomic importance, since the country is one of the world's largest producers. Among the obstacles of bean cultivation, there are diseases of biotic origin, in particular anthracnose, caused by the fungus Colletotrichum lindemuthianum, which may lead to significant losses in productivity. Resistance induction is an alternative to anthracnose control in common bean. Thus, this paper aimed to verify the efficiency of Trichoderma spp. and potassium phosphite in the control of anthracnose, evaluate and identify the anatomical and histological responses of resistance induction in common bean (P. vulgaris) in response to the attack of C. lindemuthianum, as well as to evaluate the physiological and productive aspects of the culture. The treatments consisted of two isolates, T. harzianum (TOD1 isolate) and T. virens (TM4 isolate), Fertilis™ Potassium Phosphite leaf fertilizer and treatment with distilled water (control). The inducers were applied to the bean plant alone or combined, constituting five treatments in addition to the control treatment. The six treatments were assessed in the absence and presence of C. lindemuthianum in a factorial scheme (6x2). Through the treatments, it was evaluated the anthracnose severity in bean; the anatomical and histological changes of leaf, root and stem; the contents of phenolic compounds and lignin in bean leafs; gas exchanges; location of H2O2; deposition of lignin and hypersensitivity response in hypocotyl of common bean by histochemical staining; and the agronomic parameters of the cultivation. Under greenhouse conditions, it was veryfied that potassium phosphite and combinations of Trichoderma virens and Trichoderma harzianum with potassium phosphite reduce the severity of the disease; Trichoderma virens and Trichoderma harzianum associated with potassium phosphite increase the leaflet thickness, the xylem diameter and accelerated the development of bean plant; Trichoderma virens combined with potassium phosphite increases the lignin content of the leaf; Trichoderma harzianum combined with potassium phosphite increases the rate of photosynthesis in common bean. In studies on hypocotyl, it was veryfield that Trichoderma harzianum combined with potassium phosphite accelerates the process of hypersensitivity reaction and accumulation of H2O2 in the place of pathogen penetration. Regarding the production components, treatment with Trichoderma harzianum combined with potassium phosphite promoted an increase in the number of pods/plant and in the mass of one hundred seeds. Thus, it is concluded that the combination of Trichoderma spp. and potassium phosphite promoted the development of common bean and promoted the control of anthracnose.